Mediastinal sarcoid-like reaction after colon adenocarcinoma resection. (January 2015) - Fiorelli, Alfonso; Accardo, Marina; Orditura, Michele; Santini, Mario
We report a rare case of mediastinal sarcoid-like reaction presenting 5 years after colon adenocarcinoma resection. The lack of clinical and biochemical features suggestive of sarcoidosis and the high 18 F-fluorodeoxyglucose uptake in mediastinal adenopathy, not seen previously, led us to suspect cancer recurrence. Pathological diagnosis obtained with a thoracoscopic biopsy confirmed sarcoidosis. Mediastinal adenopathies need to be confirmed pathologically to avoid potential interpretative pitfalls leading to toxic overtreatment.